Examining hedonic and utilitarian motivations for m-commerce fashion retail app engagement. Issue 4 (3rd October 2016) - Parker, Christopher J.; Wang, Huchen
Abstract : Purpose: The purpose of this paper is to explore the motivations of consumers engage with fashion retail applications (apps) from a consumer motivation perspective to inform the design for fashion retail apps. This is an area with increasing economic significance, yet of limited academic research to date. Design/methodology/approach: Through 18 in-depth qualitative interviews, utilitarian stimuli was identified as primary motivating factor to attract customers to shop for fashion garments through m-commerce retail apps. Findings: Results from thematic analysis identified that the utilitarian elements of "efficiency" and "convenience" were two of the most important motivators for engagement, with "personalized services", and "convenient operation process" also dominant functions to attract customers to shop on m-commerce retail apps. While "Social" shopping was shown to be a motivating factor for consumer behaviour, participants showed greater preference to interpersonal communications channels than to social media. Research limitations/implications: Findings from this study reveal the utilitarian focus of fashion retail apps within an industry often focussed on experiential interactions, and provide a focus for fashion retail m-commerce app designers to tailor their products for higher consumer engagement. Future apps should be designed specifically with this in mind to increase the chance of consumer engagement. Originality/value: This paper provides original insight into the hedonic and utilitarian value motivations most prevalent to users of m-commerce fashion retail apps. This is distinct from previous research that has focussed on physical retail environments or general e-commerce interactions (e.g. non-fashion web stores accessed through a PC/laptop).